Current approaches to glaucoma surgery in children – glaucoma drainage devices and minimally invasive procedures - Garbowska, Katarzyna; Modrzejewska, Monika (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
Glaucoma is one of the leading causes of visual impairment and irreversible loss of vision in children worldwide. Taking into account prolonged treatment, the condition should be diagnosed as early as possible, so that an appropriate therapeutic strategy can be implemented. The choice of treatment should be guided by factors including the type of glaucoma, the patient’s age, the condition of the anterior segment of the eye, the course of treatment to date, and the child’s general health. In many glaucoma cases in pediatric patients, surgery (goniotomy, trabeculotomy) is the first-line treatment, but in recent years more and more importance has been attached to surgical procedures involving the implantation of filtration and drainage valves as well as novel surgical techniques, including minimally invasive glaucoma surgery (MIGS) via the ab interno approach. They may provide additional or alternative solutions to traditional surgical procedures in the treatment of childhood glaucoma.